The analysis of Shopee Paylater performance among college students - Muhammad Al-Furqan; Perengki Susanto (Operations Management and Information System Studies, 2022)
This study aims to analyze the effect of performance expectancy, facilitating condition, social influence, innovativeness, perceived technology security, and hedonic motivation on adoption of Shopee Paylater on student in Padang. The population used in the study were students that know or already used Shopee Paylater mobile payment users and the sample used was students that know or already used Shopee Paylater mobile payment users in Padang. The number of samples in this study was 275 total respondents. Data was collected through online questionnaires and data processing using PLS (Partial Least Square) software. The results of this study indicate that. (1) Performance expectancy has a positive and significant impact towards adoption of Paylater. (2) Facilitating condition has a negative impact towards adoption of Paylater. (3) Social influence has positive and significant impact on adoption of Paylater. (4) Innovativeness has positive and significant impact on adoption of Paylater. (5) Perceived technology security has positive and not significant impact towards adoption of Paylater. And (6) Hedonic motivation has positive and not significant impact towards adoption of Paylater.